Hubungan Aktivitas Fisik dengan Kejadian Obesitas pada Remaja SMAN 4 Denpasar Selama Masa Pandemi Covid-19 - Komang Ayu Trisna Paramita; Suyasaning Hastiko Indonesiani; Luh Gede Pradnyawati (Aesculapius Medical Journal, 2023)
Obesity defined as a description of fat accumulation in adipose that occurs because the entry of calories into the body exceeds the body's metabolic needs. The prevalence rate of obesity in adolescents aged 10 to 19 years in 2016 has increased by more than 18%. One of the factors that cause obesity in adolescents is the lack of physical activity. Physical activity is a physical movement or exercise that arises due to muscle movement. The coronavirus disease (Covid-19) pandemic has changed people's way of life such as to become a sedentary lifestyle This study aims to assess the relationship between phe method ysical activity and obesity in SMAN 4 Denpasar during the Covid-19 pandemic. The method used was an observational analytic research and cross sectional approach. This study was conducted on 117 samples who selected by random sampling, and involved in inclusive samples Physical sctivity was measured using Physical Activity Questionnaire Adolescents (PAQ-A) while obesity was measured using Body Mass Index(BMI). Data obtained was then analysed using SPSS 22. The results were showed as follow: the light and mild physical activity : 41.0% and 59.0 %, respectively; while non obesity and obesity ; 94.8%and 13.6 %, espectively. The relationship between physical activity and incidence of adolescence obesity was significantly ( p< 0.05) The conclusion could be drawn that there was significant relationship between both above. It was recommended that the adolescence pupils should improve their physical activity.